GE_GERICHTE C/13724/2012 vom 22. Januar 2013 - GE Cour de justice (2013)
DIMINUTION DE LOYER; DOMMAGES-INTÉRÊTS | CPC.317.1; CPC.126.1; CPC.316.1; CO.82; CO.260; CO.257a.2; CO.1; CO.2; CO.259a; CO.259d; CO.259e; CPC.128.3